Analysis Of Investor Rationality Towards Stock Price Index And Optimal Portfolio In Go Public Company Shares On The Indonesian Stock Exchange - Wisnu Daru Setiawan; Mariati Tamba; Wardojo (Journal of Entrepreneur and Business, 2024)
This study aims to determine the existence of investor rationality in choosing optimal stocks and portfolios by using a single index model on company shares listed on the IDX in 2018. The type of research used is analytic research. This analytic study aims to draw general conclusions and prove hypotheses about the average difference of two independent samples. The data used are secondary data obtained from information released by the Indonesia Stock Exchange including the daily closing stock price and the daily closing stock price index of listed companies. The sample selection method used is purposive sampling, where the sample selection is done on the basis of the researchers' consideration. the number of samples used in this study were 30 samples. The results showed that there was investor rationality towards optimal ownership of shares and portfolios by using a single index model on stocks listed on the Indonesia Stock Exchange during the weakening period of the rupiah in 2018 (t count value of 2.16 or greater than t value of α of 2.13). This can be seen from the difference in the average stock trading volume where the average trading volume of the optimal portfolio candidate shares is greater than the average trading volume of shares not the optimal portfolio candidate. Keywords : Investor Rationality, Share Ownership and Optimal Portfolio